Serum Calcium, Magnesium, and Phosphorus Levels in Patients with COVID-19: Relationships with Poor Outcome and Mortality - Díez, Juan J.; Iglesias, Pedro; García, Agustín; Martín-Casasempere, Ignacio; Bernabéu-Andréu, Francisco A. (Hormone and Metabolic Research, 2022)
In this retrospective study to assess the impact of serum corrected calcium (CorrCa), magnesium (Mg) and phosphorus (P) levels, all adult patients with laboratory-confirmed COVID-19 hospitalized during 2020 were included. Poor outcome was considered in patients who presented need for mechanical ventilation, intensive care unit (ICU) admission, or in-hospital mortality. We analyzed 2473 patients (956 females) aged (mean±SD) 63.4±15.9 years. During admission, 169 patients (6.8%) required mechanical ventilation, 205 (8.3%) were admitted to the ICU, and 270 (10.9%) died. Composite variable of poor outcome, defined as need for mechanical ventilation, ICU admission or death, was present in 434 (17.5%) patients. In univariate analysis, the need for mechanical ventilation was positively related to Mg levels (OR 8.37, 95% CI 3.62–19.33; p<0.001); ICU admission was related to CorrCa (OR 0.49, 95% CI 0.25–0.99; p=0.049) and Mg levels (OR 5.81, 95% CI 2.74–12.35; p<0.001); and in-hospital mortality was related to CorrCa (OR 1.73, 95% CI 1.14–2.64; p=0.011). The composite variable of poor outcome was only related to Mg (OR 2.68, 95% CI 1.54–4.68; p=0.001). However, in multivariate analysis only CorrCa was significantly related to the need for mechanical ventilation (OR 0.19, 95% CI 0.05–0.72; p=0.014) and ICU admission (OR 0.25; 95% CI 0.09–0.66; p=0.005), but not with in-hospital mortality or the composite variable. In conclusion, CorrCa can be used as a simple and reliable marker of poor outcome in patients with COVID-19, although not to predict the risk of in-hospital mortality.
Keywords: COVID-19; calcium; magnesium; phosphorus; outcome; mortality